School Bullying Mapping for Educators in South Jakarta - Wahyuniar, Lely; Pustakasari, Endahing. N.I (Annpublisher, 2024)
This research analyzes Bullying Mapping on Educators in South Jakarta. This descriptive research method seeks to discover educators' knowledge and attitudes towards bullying in schools. The sample is educators with a distribution of school levels, namely Junior High School (24 respondents), Senior High School (SMA) / Equivalent as many as 62 respondents, and SLB B-C as many as two respondents. Cases of bullying that occurred in several schools in South Jakarta based on the knowledge of educators who were respondents concluded that most of them never happened, followed by occasional occurrences. Most of the forms of bullying that commonly occur in schools are in the form of cyberbullying, verbal, social, violent, and psychological violence. So, educators and students need to receive further education about anti-bullying.